2001
DOI: 10.1073/pnas.171305098
|View full text |Cite
|
Sign up to set email alerts
|

The Eurasian Heartland: A continental perspective on Y-chromosome diversity

Abstract: The nonrecombining portion of the human Y chromosome has proven to be a valuable tool for the study of population history. The maintenance of extended haplotypes characteristic of particular geographic regions, despite extensive admixture, allows complex demographic events to be deconstructed. In this study we report the frequencies of 23 Y-chromosome biallelic polymorphism haplotypes in 1,935 men from 49 Eurasian populations, with a particular focus on Central Asia. These haplotypes reveal traces of historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
391
3
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(438 citation statements)
references
References 24 publications
(39 reference statements)
35
391
3
5
Order By: Relevance
“…Further, M17-R1a (presently designated as R1a1) was suggested as a potential marker with decreasing frequencies from Central Asia towards South India. 23 On similar lines, it was suggested that a package of Y-HGs (J2, R1a, R2 and L) was associated with the migration of Indo-European people from Central Asia. 7 Although our study observed a high frequency of Y-HGs, R1a1, J*/J2, R2 and L, it was not exclusively restricted to any region or population (Table 1).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, M17-R1a (presently designated as R1a1) was suggested as a potential marker with decreasing frequencies from Central Asia towards South India. 23 On similar lines, it was suggested that a package of Y-HGs (J2, R1a, R2 and L) was associated with the migration of Indo-European people from Central Asia. 7 Although our study observed a high frequency of Y-HGs, R1a1, J*/J2, R2 and L, it was not exclusively restricted to any region or population (Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…To substantiate our data and compare our results, we further compiled the data available in the literature for Indian populations (400 Brahmin Y-chromosomes as well as 1788 scheduled caste/tribal Y-chromosomes). 7,9,12,21,23,24,29 as well as for other population groups, mainly from Central Asia, Eurasia and Southeast Asia. 9,23,[30][31][32][33][34] Sample collection and DNA isolation About 2 ml of venous blood was collected from each individual, with their informed written consent and the approval of Jawaharlal Nehru University ethical committee.…”
Section: Samples Analyzedmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]29,30 This haplogroup is thought to have originated in Central Asia approximately 40 000 years BP and then migrated westward into Europe, achieving its highest frequencies in the western region of this continent. 39,40 Although Balaresque et al 41 proposed the hypothesis of a European spread of haplogroup R1b1b2-M269 during the Neolithic, the distribution of the M269 sub-haplogroups and their Y-STR diversities proved to be compatible with a pre-Neolithic diffusion of M269 in Europe. 42,43 The reported high frequencies of this haplogroup in Central-West Africa led to the proposal of a 'back to Africa' migration as the justification for the otherwise unexpected presence of this haplogroup in the region.…”
Section: Characterisation Of the Male Lineages Of Equatorial Guineamentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] These studies were mostly based on sequences of the first hypervariable segment of the noncoding mtDNA control region (HV1) and Y chromosome binary marker variation in various groups from this region. mtDNA studies reveal a high level of diversity, exceeding that within all of Europe and only slightly lower than West Asian mtDNA diversity, which might indicate an old age of human populations from this region.…”
Section: Introductionmentioning
confidence: 99%